Amino Alcohols as Potential Antibiotic and Antifungal Leads - Jennifer R. Baker; Peter J. Cossar; Mark A. T. Blaskovich; Alysha G. Elliott; Johannes Zuegg; Matthew A. Cooper; Peter J. Lewis; Adam McCluskey (Molecules, 2022)
Five focused compound libraries (forty-nine compounds), based on prior studies in our laboratory were synthesized and screened for antibiotic and anti-fungal activity against S. aureus, E. coli, K. pneumoniae, P. aeruginosa, A. baumannii, C. albicans and C. neoformans. Low levels of activity, at the initial screening concentration of 32 μg/mL, were noted with analogues of (Z)-2-(3,4-dichlorophenyl)-3-phenylacrylonitriles which made up the first two focused libraries produced. The most promising analogues possessing additional substituents on the terminal aromatic ring of the synthesised acrylonitriles. Modifications of the terminal aromatic moiety were explored through epoxide installation flowed by flow chemistry mediated ring opening aminolysis with discreet sets of amines to the corresponding amino alcohols. Three new focused libraries were developed from substituted anilines, cyclic amines, and phenyl linked heterocyclic amines. The aniline-based compounds were inactive against the bacterial and fungal lines screened. The introduction of a cyclic, such as piperidine, piperazine, or morpholine, showed >50% inhibition when evaluated at 32 μg/mL compound concentration against methicillin-resistant Staphylococcus aureus. Examination of the terminal aromatic substituent via oxirane aminolysis allowed for the synthesis of three new focused libraries of afforded amino alcohols. Aromatic substituted piperidine or piperazine switched library activity from antibacterial to anti-fungal activity with ((Z)-2-(3,4-dichlorophenyl)-3-(4-(2-hydroxy-3-(4-methylpiperazin-1-yl)propoxy)phenyl)acrylonitrile), ((Z)-2-(3,4-dichlorophenyl)-3-(4-(2-hydroxy-3-(4-(4-hydroxyphenyl)piperazin-1-yl)propoxy)-phenyl)acrylonitrile) and ((Z)-3-(4-(3-(4-cyclohexylpiperazin-1-yl)-2-hydroxypropoxy)-phenyl)-2-(3,4-dichlorophenyl)-acrylonitrile) showing >95% inhibition of Cryptococcus neoformans var. grubii H99 growth at 32 μg/mL. While (Z)-3-(4-(3-(cyclohexylamino)-2-hydroxypropoxy)phenyl)-2-(3,4-dichlorophenyl)-acrylonitrile, (S,Z)-2-(3,4-dichlorophenyl)-3-(4-(2-hydroxy-3-(piperidin-1-yl)propoxy)phenyl)acrylonitrile, (R,Z)-2-(3,4-dichlorophenyl)-3-(4-(2-hydroxy-3-(piperidin-1-yl)propoxy)phenyl)acrylonitrile, (Z)-2-(3,4-dichlorophenyl)-3-(4-(2-hydroxy-3-(D-11-piperidin-1-yl)propoxy)phenyl)-acrylonitrile, and (Z)-3-(4-(3-(4-cyclohexylpiperazin-1-yl)-2-hydroxypropoxy)-phenyl)-2-(3,4-dichlorophenyl)-acrylonitrile 32 μg/mL against Staphylococcus aureus.